Is loneliness a bridge to digital escape? A path analysis on psychological symptoms and internet addiction - Bilgin, Okan; Ince, Murat; Colakoglu, Ozgur Murat (FRONTIERS MEDIA SA, 2026)
Introduction Internet addiction has become a significant public health concern that threatens individuals' psychological well-being. This study aimed to examine the effects of psychological symptoms (somatization, hostility, negative self-concept, depression, and anxiety) on internet addiction and to explore the mediating role of loneliness.Methods Using a correlational survey design, data were collected from 1,404 university students across different academic disciplines. Psychological symptoms, internet addiction, and loneliness were measured using the Brief Symptom Inventory, the Internet Addiction Scale, and the ULS-8 Loneliness Scale. Structural equation modeling with bootstrapping procedures was employed.Results The results indicated that participants reported moderate levels of internet addiction and low levels of loneliness. The effects of somatization, hostility, negative self-concept, and depression on internet addiction were fully mediated by loneliness. Negative self-concept showed the strongest effect on loneliness. In contrast, anxiety did not have a significant effect on loneliness but exerted a strong direct effect on internet addiction.Discussion These findings suggest that loneliness may function as a key intermediary variable linking psychological symptoms to internet addiction, whereas anxiety may exert a more direct influence. The results highlight the importance of tailored interventions addressing both loneliness and anxiety in preventing internet addiction.
Keywords: internet addiction; loneliness; psychological symptoms; structural equation modeling; university students; SUBSTANCE USE; DEPRESSION; PSYCHOPATHOLOGY; PERSONALITY; ASSOCIATION; VALIDITY; HEALTH; SCALE; Psychology